Manajemen Pembelajaran Dalam Meningkatkan Kecerdasan Siswa di MA Al-Fatah Palembang - Halin, Tika; Tri Rahayu, Yunita; Akhmad Saputra , Ade (MindSet : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to improve the intelligence of students at MA Al-Fatah Palembang. The subjects of this study were school principals, teachers and students. data obtained through observation, interviews, and documentation. This research was contucted so that students at MA Al-Fatah Palembang  can change the quality of the students themselves through an education because at this time education prioritizes intellectual aspects as a measure of success.